Chloride Ions in the Pore of Glycine and GABA Channels Shape the Time Course and Voltage Dependence of Agonist Currents - Moroni, Mirko (Society for Neuroscience, 2011)
In the vertebrate CNS, fast synaptic inhibition is mediated by GABA and glycine receptors. We recently reported that the time course of these synaptic currents is slower when intracellular chloride is high. Here we extend these findings to measure the effects of both extracellular and intracellular chloride on the deactivation of glycine and GABA currents at both negative and positive holding potentials. Currents were elicited by fast agonist application to outside-out patches from HEK-293 cells expressing rat glycine or GABA receptors. The slowing effect of high extracellular chloride on current decay was detectable only in low intracellular chloride (4 mm). Our main finding is that glycine and GABA receptors “sense” chloride concentrations because of interactions between the M2 pore-lining domain and the permeating ions. This hypothesis is supported by the observation that the sensitivity of channel gating to intracellular chloride is abolished if the channel is engineered to become cation selective or if positive charges in the external pore vestibule are eliminated by mutagenesis. The appropriate interaction between permeating ions and channel pore is also necessary to maintain the channel voltage sensitivity of gating, which prolongs current decay at depolarized potentials. Voltage dependence is abolished by the same mutations that suppress the effect of intracellular chloride and also by replacing chloride with another permeant ion, thiocyanate. These observations suggest that permeant chloride affects gating by a foot-in-the-door effect, binding to a channel site with asymmetrical access from the intracellular and extracellular sides of the membrane.